Surviving the Anthropocene: Climate Change and Environmental Collapse in Octavia Butler’s Parable of the Sower - Dounya BOUREZG; . Karima Laouidji (كلية الاداب و اللغات, 2025)
This dissertation investigates how environmental collapse, social decline, and climate change manifest in Octavia E. Butler’s Parable of the Sower (1993). It also seeks to examineresilience and the survival strategies developed by Butler’s characters to cope with ecological devastation, social instability, and personal vulnerability. To achieve this end, Butler’s narrative is analyzed through the ecocritical lens, with particular attention to ecodystopian themes, Anthropocene studies and resilience studies. It also draws on concepts of adaptation and survival to analyze the ways Lauren Olamina and her community respond to climateinstability and existential threats. This research reveals that Parable of the Sower portrays environmental decline not only as an ecological crisis but also as a psychological, social, and spiritual challenge, whichrequires transformation, community-building, and resilience. Ultimately, this dissertation hopes to make significant contributions to Anthropocene studies, ecocritical literature, and the growing field of dystopian and climate
Keywords: Keywords: Anthropocene; climate change; ecodystopia; resilience; adaptation; environmental collapse.